Is Partially Thrombosed False Lumen Really a Predictor for Adverse Events in Uncomplicated Type B Aortic Dissection: A Systematic Review and Meta-Analysis? - Wu, Jinlin; Song, Jian; Li, Xin; Yang, Jue; Yu, Changjiang; Zhou, Chenyu; Sun, Tucheng; Fan, Ruixin (Frontiers in Cardiovascular Medicine, 2022)
Objective: This meta-analysis and systematic review investigated whether partial thrombosed false lumen was a predictor for adverse events in uncomplicated Type B aortic dissection (TBAD). Methods: We performed the current systematic review of the medical literature according to the 2009 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The Newcastle-Ottawa Scale was used to evaluate the quality of individual studies. Search terms based on the MEDLINE database included “type B aortic dissection”, “false lumen” and “thrombosis”. The primary outcomes included mortality, intervention, and aortic growth. Results: 6 studies were included in this systematic review, with a total number of 692 patients, including 197 patency (28.5%), 214 partial thrombosis (30.9%)，and 281 complete thrombosis (40.6%). Due to the insufficient data for quantitative analysis, we only conducted a scoping review for mortality and intervention. For aortic growth, we conducted a meta-analysis based on Standardized Mean Difference (SMD). The SMD of PT versus P by random effect model was -0.05 (random effect model) (95% confidence interval (CI), -0.39-0.29). The 95% CI crossed with the null line of 0, indicating no significant difference. The SMD was 0.37 (fixed effects model) (95% CI, 0.03-0.71) and 0.70 (fixed effects model) (95% CI, 0.37-1.04) for PT versus CT, and P versus CT, respectively. Conclusions: Current researches on partial thrombosis of TBAD are inconsistent. Partial thrombosis is not associated with a faster aortic growth rate. Until more solid evidence is available, we do not recommend partial thrombosis as a surgical indication or high-risk profile for TBAD.